Dynamic and Accurate Characteristics of Extremal Automation Control System of Step- By-Step and Compensating Interferometer - I. F. Touzkov (Наука и техника)
Extremal automation control system of step-by-step and compensating interferometer has been considered on the basis of automation control theory. An error arising due to non-suppressed variable of the signal component at the output of low frequency filter has been calculated. The transient process of the investigated system has been analyzed with the help of MATLAB/Simulink program-simulated complex.